Using intermittent pulse oximetry to guide neonatal oxygen therapy in a low-resource context. Issue 3 (28th August 2019) - Walker, Patrick James Berkeley; Bakare, Ayobami Adebayo; Ayede, Adejumoke Idowu; Oluwafemi, Rosena Olubanke; Olubosede, Omolayo Adebukola; Olafimihan, Iyabo Victoria; Tan, Kenneth; Duke, Trevor; Falade, Adegoke Gbadegesin; Graham, Hamish
Abstract : Objective: To evaluate the effectiveness of intermittent pulse oximetry in guiding oxygen therapy in neonates in a low-resource setting. Design and setting: Prospective validation study at three hospitals in southwest Nigeria. We performed concealed continuous pulse oximetry on participants to evaluate intermittent SpO2 monitoring. Patients: We recruited all preterm or low birthweight neonates, and all term neonates who required oxygen therapy, who were admitted to the neonatal ward(s) of the study hospitals during the study period. Main outcome measures: Proportion of time preterm/low birthweight neonates on oxygen spent within, above and below the target SpO2 range of 90%–95%; and the proportion of time term neonates and neonates not on oxygen spent within and below the target range of 90%–100%. Results: Preterm/low birthweight neonates receiving oxygen therapy (group A) spent 15.7% (95% CI 13.3 to 18.9) of time in the target SpO2 range of 90%–95%. They spent 75.0% (63.6–81.1) of time above 95%, and 2.7% (1.7–5.6) of time below 85%. Term neonates and all neonates not receiving oxygen (group B) spent 97.3% (95% CI 96.4 to 98.6) of time within the target range of 90%–100%, and 0.9% (0.3–1.4) of time below 85%. Guidelines recommended SpO2 monitoring 3 times per day for all patients, however neonates in groups A and B were monitored an average of 4.7 and 5.3 times per day, respectively. Conclusions: To better maintain SpO2 within the target range, preterm/low birthweight neonates on oxygen should have their SpO2 monitored more frequently than the current 4.7 times per day. In all other neonates, however, monitoring SpO2 5.3 times per day appears suitable.